Do Islamic Work Ethic and Shariah Marketing Mix Influence Muzakki Loyalty via Institutional Image? - Fikriyah, Khusnul; Kusaeri, Kusaeri; Ritonga, Iskandar (ZISWAF, 2024)
This study aims to examine both the direct and indirect effect of Islamic work ethic and sharia marketing mix variables on muzakki loyalty with institutional image serving as a mediating element. This examination was conducted at Amil Zakat Institution in East Java using quantitative methods. Data Collection was carried out using a survey method via questionnaire distributed to muzakki of Amil Zakat Institution in East Java. Subsequently, the data was further processed using SmartPLS 4. The results showed that both Islamic Work Ethic and Sharia marketing mix had a positive and significant direct effect on muzakki loyalty. Furthermore, indirect testing with institutional image as a mediating variable showed that Islamic Work Ethic and Sharia marketing mix positively and significantly influenced muzakki loyalty. These discoveries could be applied to improve zakat institution management, particularly in marketing and human resources, thereby enhancing muzakki loyalty and potentially increasing national zakat receipts in the long term.